Eksistensi Bissu dalam Masyarakat Suku Bugis Studi Kasus Bissu di Segeri Kabupaten Pangkep: Eksistensi Bissu dalam Masyarakat Suku Bugis: Studi Kasus Bissu di Segeri Kabupaten Pangkep - Rahmat Rahmat; Muhammad Saleh; Mahyuddin; St Aminah Azis (IAIN Parepare, 2023)
The Existence of the Bissu Community in Bugis Society with a Case Study in Segeri District, Pangkep Regency. Bissu is a community. Bissu are considered priests who are biologically a mixture of men and women, whose gender is considered to consist of a mixture of men and women in Bugis tribal society. This research basically aims to describe and analyze the existence or whereabouts of the Bissu community in Segeri District and the role of this community in society in Segeri District, Pangkep Regency. This research uses a descriptive qualitative method with a case study approach. Data collection techniques in this research are initial observation, interviews with informants and documentation. Meanwhile, data analysis techniques in this research use analysis such as data reduction, data presentation and drawing conclusions. The research results show that the existence of the Bissu community in society in Segeri District cannot be separated from their social role as a Bissu community in society, which is the reason they still survive. The large role of the government and the surrounding community in supporting ritual activities such as traditional ceremonies and traditions of the Bissu community which are currently still being carried out. The Bissu community plays a large role in society, for example as holders of customs and rituals, as well as custodians of Arajang. Bissu also plays the role of Indo Botting (Bridal Makeup Artist), also in wedding celebration activities, and also as Sandro who can cure all illnesses by praying.